ANTI-ATHEROSCLEROTIC ACTIVITY OF ETHANOLIC EXTRACT OF CHRYSANTHEMUM INDICUM L. FLOWERS AGAINST HIGH-FAT DIET-INDUCED ATHEROSCLEROSIS IN MALE WISTAR RATS - P, Sravanthi; S, Shakir Basha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of the present study was to evaluate the anti-atherosclerotic activity of ethanolic extract of Chrysanthemum indicum (EECI) flowers against high-fat diet induction in male Wistar rats. Methods: The method used for induction of atherosclerosis was high-fat diet for 28 days. Rats were divided into five groups (n=6). Group I served as normal. Group II serves as high-fat diet-treated group. Group III serves as standard treated with high-fat diet+atorvastatin (30 mg/kg, p.o). Group IV serves as low dose treated with high-fat diet+EECI (150 mg/kg, p.o.). Group V serves as high dose treated with high-fat diet+EECI (300 mg/kg, p.o.). The following parameters, glucose, high-density lipoprotein (HDL), low-density lipoprotein (LDL), total cholesterol (TC), very LDL (VLDL), triglycerides (TG), atherogenic index (AI), serum glutamic oxaloacetic transaminase, serum glutamic pyruvic transaminase, total protein, food consumption, and body weight, were evaluated and histopathological studies were performed. Results: The results showed that EECI at a dose of 150 mg/kg and 300 mg/kg exhibited significant decrease in glucose, TG, TC, LDL-cholesterol (LDL-C), HDL, VLDL, AI, and total protein levels when compared to high-fat diet group. This investigation reveals that the extract-treated groups lower the serum TC and LDL-C levels significantly, which reduces the risk of coronary heart disease. Conclusion: The experimental studies show that the EECI of both doses 150 mg/kg and 300 mg/kg, respectively, showed significant reduction in lipid profile, glucose, and total protein. From the study, the plant extract showed anti-atherosclerotic activity and thus authenticates its ethnomedicinal use.